STRATEGI PENGUATAN KARAKTER DEMOKRATIS MELALUI PEMBELAJARAN PPKn BERBASIS PROYEK PADA SISWA KELAS XI DI SMA NEGERI KEBAKKRAMAT - Dwiyanti, Devi; Muchtarom, Moh.; Winarno, Winarno (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to describe democratic character reinforcement strategy and democratic character which is shown by students as the impact of the implementation of project based civic education learning. This study uses qualitative method with descriptive qualitative approach. Data source of this research involves informant (civic education teachers, class XI students and alumnus of SMA Negeri Kebakkramat), project based civic education learning activities and documents (Lesson plan, score list, and Project based civic education learning product result). Sampling technique uses purposive sampling and snowball sampling. Data collection uses participatory observation technique, document analysis and deep interview directly. Validity test technique uses triangulation of methods and data sources. Data analysis uses interactive analysis technique. Research results is democratic character reinforcement strategy which is done by civic education teachers through project based civic education learning with provide exemplary democratic character values in every steps of project based civic education learning accordance with the material Beware of Threats Against the Unitary State of the Republic of Indonesia. Democratic character which is evidenced by the attitude of studentswho obey the rules and regulations at school and do every assignmentgiven by the teacher, both individually and in groups of project based civic education learning.